Effect of pre-anesthetic fasting on gastric emptying and plasma glucose in healthy dogs of different age groups - Lecheta,Danielle R. (2020)
ABSTRACT: Gastric emptying and plasma glucose were evaluated in young and adult dogs, fed with dry and wet food, submitted to different periods of pre-anesthetic fasting (6, 8, and 12 hours). Forty healthy dogs were selected, which were segmented into four groups according to the age group and type of diet. It was evaluated the gastric emptying by ultrasound and serum glycemia. Only 17.5% presented complete gastric emptying, and no significant differences were found between the 6 and 8-hour fasting evaluations, or between the age groups and the diets, considering significance level p<0.05. Mean plasma glucose values from the groups indicated normal glycemia at all times of evaluation. A significant difference was found between the means of glycemia in young and adult dogs, with the 8-hour fasting with wet diet (p=0.03) and with 12 hours with dry diet (p=0.04). Healthy young and adult dogs, in physiological equilibrium, maintain average values of plasma glucose despite prolonged periods of pre-anesthetic fasting, which may be necessary, since 8-hour fasting for solid food is not enough to provide complete gastric emptying.